(untitled) (Indian Journal of Animal Production and Management, 2013)
The study was conducted in Jhunjhunu district of Rajasthan to find out the various constraints faced by the respondents in adoption of recommended milk production, calf rearing and housing management practices. The results of the study revealed that low price of milk and ghee (1.62 MS), lack of market for milk products (1.47 MS), low economic gain (1.17 MS) and lack of knowledge about milk processing (1.16 MS) were the major constraints in management practices of milk production. The overall constraint in milk production practices mean score was 1.04. Lack of knowledge about milk replacer to the calves (1.36 MS), prevalence of belief that colostrum feeding to calf before placenta drops decrease the milk production (1.29 MS), lack of awareness about right time and scientific method of castration (1.18 MS) and lack of knowledge about deworming practices (1.04 MS) were found as the serious constraints in calf rearing management practices. The overall calf rearing management practices mean score was 0.97. Regarding constraints in housing management practices, high cost investment in construction of scientific dairy shed (1.43 MS), inadequate credit facilities (1.33 MS), scarcity of regular electric supply (1.20 MS) and lack of cheap and scientific cattle shed model (1.06 MS) were the major constraints. The overall housing management practices mean score was 1.03. To overcome these constraints, establishment of milk processing unit, strengthening the network of co-operative dairy, recognition of superior breed calf, Kamdhenu Aawas Yojna and Cattle Credit Card should be promoted.